Perbandingan Derajat Keparahan Acne Vulgaris pada Pasien yang Menjalani Superficial Chemical Peeling di Klinik Kecantikan di Batubulan, Gianyar - Putu Ayu Danys Rania; I Gde Nengah Adhilaksman Sunyamurthi Wirawan; Ni Wayan Winianti (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
Acne vulgaris is a skin disease that is often found in women. Various kinds of treatment are given to sufferers of acne vulgaris to cure and get rid of acne. Currently, the therapy that is being intensively used to cure acne vulgaris is chemical peels. Giving chemical peels is believed to reduce acne scars and inflammatory and non-inflammatory lesions, improve depigmentation, and eliminate scar tissue caused by acne. The purpose of this study was to compare the severity of acne vulgaris based on the frequency and regularity of patients undergoing superficial chemical peels at the Batubulan beauty clinic, Gianyar. This research is a descriptive study with a cross sectional approach. The research population used was acne vulgaris sufferers who underwent treatment at a beauty clinic in Batubulan, Gianyar, with a total of 34 samples. The results showed that most of the patients who underwent superficial chemical peels at the Batubulan beauty clinic, Gianyar were women aged 17-30 years with a frequency of 6-12 superficial chemical peels, 17 people (50.0%), 13 people-24 times, 15 times. people (44.1%), and >24 times as many as 2 people (5.9%) which was done once a month by 12 people (35.3%) and twice a month by 22 people (64.7%) with mild degrees 28 people (82.4%) and 6 people (17.6%). Patients with a mild degree of acne mostly underwent superficial chemical peels 6-24 times and patients with mild degrees of acne mostly underwent superficial chemical peels twice a month.